2006
DOI: 10.1007/s00259-006-0207-2
|View full text |Cite
|
Sign up to set email alerts
|

Sixty-four slice spiral CT angiography does not predict the functional relevance of coronary artery stenoses in patients with stable angina

Abstract: Sixty-four slice MDCT angiography failed to predict the functional relevance of CAS, but had a high negative predictive value in the exclusion of functionally relevant CAS in symptomatic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
1
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 20 publications
8
56
1
3
Order By: Relevance
“…Observation from 64-slice CTA provides high-quality noninvasive coronary arteriogram that accurately delineates the presence or absence of significant stenotic lesion within entire coronary trees [4,5]. However recent reports showed that CTA does not predict the functional relevance of coronary artery stenoses in patients with stable angina in accordance with our result [7,22]. The potential clinical value of such information remains to be elucidated.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Observation from 64-slice CTA provides high-quality noninvasive coronary arteriogram that accurately delineates the presence or absence of significant stenotic lesion within entire coronary trees [4,5]. However recent reports showed that CTA does not predict the functional relevance of coronary artery stenoses in patients with stable angina in accordance with our result [7,22]. The potential clinical value of such information remains to be elucidated.…”
Section: Discussionsupporting
confidence: 73%
“…The potential clinical value of such information remains to be elucidated. Therefore, the policy of proceeding directly with CTA stenosis for the intervention results in subjecting patients to a higher number of cardiac events, since CTA stenosis is irrelevant with 14 functional ischemia, as shown in this study [3,7,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress testing provides additional information to predict the functional relevance of coronary stenosis with respect to myocardial ischemia. 5,6 When cCTA demonstrates coronary stenosis of uncertain hemodynamic significance, a follow-up stress test may evaluate the functional significance of CAD found by cCTA. Given the divergent emphasis of stress testing on functional physiology and cCTA on coronary anatomy, these two modalities may provide complementary information in the evaluation of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the superior performance characteristics of 64-slice CCT in terms of spatial and temporal resolution lead to measurable improvements in image quality (25). Recent studies reported sensitivities and specificities of 73%-95% and 95%-99%, respectively, for 64-slice scanners (26)(27)(28). The number of segments that cannot be evaluated has been reduced to below 10% in most studies, a finding also representing a significant improvement over the performance of older scanners (Fig.…”
Section: Coronary Angiographymentioning
confidence: 83%